A Previously Unknown Building Structure in Ancient Olympia (Western Peloponnese, Greece) Revealed by Geoarchaeological Investigations and Its Interpretation as a Possible Harbor - Lena Slabon; Sarah Bäumler; Elena Appel; Sabine Fiedler; Peter Fischer; Lea Obrocki; Georg Pantelidis; Sascha Scherer; Benedict Thein; Timo Willershäuser; Birgitta Eder; Hans-Joachim Gehrke; et al. (Heritage)
The ancient site of Olympia is located on the northern fringe of the Basin of Makrisia at the confluence of the Kladeos and Alpheios rivers (western Peloponnese, Greece) and was used as a venue for the Panhellenic Games from Archaic times until the 4th century AD. Geophysical prospection (frequency domain electromagnetic induction and electrical resistivity tomography) was carried out as a basis for detailed geoarchaeological investigations. In doing so, we identified a previously unknown building structure adjacent to the Altis, the inner part of the sanctuary at Olympia. Situated south of the Southwest Thermae, this structure measures at least 100 m (WSW-ENE) by 80 m (NNW-SSE). Its external orientation is in line with the orientation of the Southwest Thermae and the Leonidaion. We retrieved sediment cores from 17 different locations in combination with high-resolution direct push sensing from inside the newly found structure. All cores revealed distinct units of organic-rich limnic sediments dominated by clay and fine silt. Geochemical and micropaleontological analyses of selected sediment samples indicate highly eutrophic conditions, as evidenced by elevated phosphorous concentrations and the dominance of the ostracod species Cyprideis torosa, which is able to live under low-oxygen conditions. Moreover, molecular biomarker analyses show a significant input of lipid fecal markers, implying strong anthropogenic pollution. Further, the limnic sediments include numerous charcoal remains and abundant diagnostic artifacts such as ceramic fragments and building material. Radiocarbon dating documents that these limnic conditions persisted within the building structure from at least the 5th century BC to the 6th century AD. The identified building structure lies in the immediate proximity to the Lake of Olympia, which was recently found to have existed from the mid-Holocene to the Medieval period. Its characteristic filling with fine-grained sediments and multiple indications for a strongly polluted and heavily used standing water environment let us hypothesize that it was possibly used as a harbor installation. A harbor at ancient Olympia could have been used to reach the sanctuary by boat and to transport goods of all kinds.